2019
DOI: 10.1111/apt.15116
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: review of donor features, procedures and outcomes in 168 clinical studies of faecal microbiota transplantation

Abstract: Summary Background Faecal microbiota transplantation (FMT) is effective for Clostridium difficile infections (CDI) refractory to standard treatment and is being studied in other diseases. Aim To evaluate donor characteristics, procedures and clinical outcomes of FMT. Methods We systematically reviewed FMT studies published up to 29 August 2018 using MEDLINE (R) and EMBASE and identified clinical studies with FMT donor information. We reported data on donor characteristics, screening criteria, administration, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 53 publications
4
89
0
6
Order By: Relevance
“…2,8 Fecal microbiota transplantation (FMT) is a highly effective therapy for patients with recurrent C. difficile infection, with a greater than 90% success rate. [9][10][11][12] Emerging evidence suggests that FMT may also have therapeutic benefits in other conditions associated with perturbed gut microbiota, including ulcerative colitis, [13][14][15][16] Crohn's disease, 17 irritable bowel syndrome, 18 metabolic syndrome, 19,20 multiple sclerosis, 21,22 depression, 23 and autism. 24,25 Intense interest in FMT is evident, with over 250 clinical trials registered on of January 11, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…2,8 Fecal microbiota transplantation (FMT) is a highly effective therapy for patients with recurrent C. difficile infection, with a greater than 90% success rate. [9][10][11][12] Emerging evidence suggests that FMT may also have therapeutic benefits in other conditions associated with perturbed gut microbiota, including ulcerative colitis, [13][14][15][16] Crohn's disease, 17 irritable bowel syndrome, 18 metabolic syndrome, 19,20 multiple sclerosis, 21,22 depression, 23 and autism. 24,25 Intense interest in FMT is evident, with over 250 clinical trials registered on of January 11, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota-targeted interventions may prove to be an effective and innovative approach for treating NAFLD. FMT has been shown to be effective in the treatment of severe gastrointestinal diseases [30]. Le Roy et al [31] showed that susceptibility to the development of NAFLD was transmissible via FMT between mice, indicating a potential causative role for gut microbial dysbiosis in the occurrence or evolution of the hepatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Dazu gehört auch, dass FMT-Sets für die Selbsttherapie im Internet erhältlich sind, auch wenn (oder vielleicht weil) es inzwischen Standards und ethisch-rechtliche Regelungen in den meisten Ländern gibt. Voraussetzung für eine wissenschaftliche Weiterentwicklung dieser Therapie sind sicherlich präzisere Informationen darüber, wann und unter welchen Konditionen FMT wirksam ist [46]. [22].…”
Section: Austausch Der Mikrobiotaunclassified